Determinants of urban environmental quality in Morocco: The roles of energy consumption, urbanization, manufacturing, and financial development in achieving SDG 13 - Bajja, Salwa; Radoine, Hassan; Abbas, Shujaat; Dakyaga, Francis; Chenal, Jerome (Frontiers in Environmental Science, 2023)
Studies on urban environmental quality are evolving emphasizing the need for policy response regarding the enactment of environmental regulations to attain sustainable development goals (SDGs), mainly target 13. Over the years, the concerns to improve the urban environmental quality and manage noise, air quality, water, sanitation, and waste have increased. Consequently, limited studies exist on the determinant of urban environmental quality. This paper attempts to build on existing studies of environmental quality, by analyzing the determinants of environmental quality in urban Morocco in the context of important factors, such as energy consumption, urbanization, manufacturing, and financial development. The study draws on time series data covering the period from 1971 to 2019 and uses Autoregressive Distributed Lag (ARDL) approach to analyze the impacts of per capita income, energy consumption, urbanization, manufacturing value-added, capital investment, and financial development on CO2. The findings of this research study reveal both short-run and long-run associations between these variables in Morocco. Nevertheless, manufacturing activities and financial development significantly deteriorate Moroccan environmental quality in the long-run. The findings suggest that efforts towards improving environmental quality in urban Morocco require the development and implementation of urban policies that advocate for the adoption and advancement of sustainable energy sources.